Preaching to the Future : Religious Schools, Youth Organizations, and the Rise of Political Islam in Türkiye - Benzer, Tolga; Tukiainen, Janne (Finland, 2026)
We examine whether anti-establishment outsider movements can leverage education and youth mobilization to build long-run political power. We study the expansion of state-run religious secondary schools in 1970s Türkiye and show that access to these schools catalyzed the emergence of Islamist youth organizations, which played a central role in ideological formation, grassroots mobilization, and the eventual electoral success of the Islamist movement. Using a novel dataset and a difference-in-differences framework, we show that access to religious schools increased the local presence of Islamist youth organizations in the short run and boosted Islamist party vote share in the medium run. Effects were strongest where youth branches formed soon after school access and engaged in ideologically immersive activities. Individuallevel survey evidence shows that exposed male cohorts were more religious and more likely to engage in Islamist party politics later in life. Our findings illustrate how schools and youth organizations—when strategically aligned—can serve as a foundation for enduring political transformation, not only for ruling elites but also for outsider movements seeking to gain power.